Varda’s Chiasmic Hand: Les Glaneurs et la Glaneuse (2000), Les plages d’Agnès (2008) and Merleau-Ponty’s intersubjective relation - Kierran Horner (Mise au Point)
This article argues that there is an alliance between Agnès Varda’s digital films, Les Glaneurs et la Glaneuse (2000) and Les plages d’Agnès (2008), and the chiasmic overlap as it occurs in Maurice Merleau-Ponty’s philosophy. This fusion, which I will show occurs through the camera and the intersubjective relation represented by Varda’s own hands, leads to the spectator’s contemplation of the death of the Other.